Antiseptic nanocapsule formation via controlling polymer deposition onto water-in-oil miniemulsion droplets - Umaporn Paiphansiri (2018)
The stable nanodroplet was prepared by inverse miniemulsion with an aqueous antiseptic solution dispersed in an organic medium of solvent/nonsolvent mixture containing an oil-soluble surfactant and the polymer for shell formation. The change in gradient of the solvent/nonsolvent mixture, obtained by heating at 50 °C, led to the precipitation of the polymer in the organic phase and deposition onto the large interphase of the aqueous miniemulsion droplets. The monodisperse polymer nanocapsule, with the size range of 80-240 nm, dispersed in cyclohexane phase was achieved as a function of surfactant concentration. By variation of polymer content, molecular weight and type, an encapsulation efficiency of 20-100% was obtained as detected by proton-nuclear magnetic resonance spectroscopy measurement. The nanocapsule could be easily transferred into water as continuous phase resulting in aqueous dispersion with nanocapsule containing the antiseptic agent as an aqueous core. The encapsulated amount of the antiseptic agent was evaluated to indicate the durability of the nanocapsule's wall. Additionally, the different types of polymer having glass transition temperature ranging from -60 to 100°C have been successfully used. Currently, the research work on the incorporation of nanocapsules onto natural rubber (NR) latex in order to prepare NR latex glove containing the antiseptic agent nanocapsules is carried out. By using the simple and versatile layer-by-layer (LbL) technique based mainly on an electrostatic interaction between oppositely charged species, the deposition of nanocapsules onto NR latex film has successfully been fulfilled. Copyright © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.